Ankyrin G Membrane Partners Drive the Establishment and Maintenance of the Axon Initial Segment - Leterrier, Christophe; Clerc, Nadine; Rueda-Boroni, Fanny; Montersino, Audrey; Dargent, Bénédicte; Castets, Francis (Frontiers in Cellular Neuroscience, 2017)
The axon initial segment (AIS) is a highly specialized neuronal compartment that plays a key role in neuronal development and excitability. It concentrates multiple membrane proteins such as ion channels and cell adhesion molecules (CAMs) that are recruited to the AIS by the scaffold protein ankyrin G (ankG). The crucial function of ankG in the anchoring of AIS membrane components is well established, but a reciprocal role of membrane partners in ankG targeting and stabilization remained elusive. In rat cultured hippocampal neurons and cortical organotypic slices, we found that shRNA-mediated knockdown of ankG membrane partners (voltage-gated sodium channels (Nav) or neurofascin-186) led to a decrease of ankG concentration and perturbed the AIS formation and maintenance. These effects were rescued by expressing a recombinant AIS-targeted Nav or by a minimal construct containing the ankyrin-binding domain of Nav1.2 and a membrane anchor (mABD). Moreover, overexpressing mABD in mature neurons led to ankG mislocalization. Altogether, these results demonstrate that a tight and precocious association of ankG with its membrane partners is a key step for the establishment and maintenance of the AIS.